TATA KELOLA PERUSAHAAN (CG) DAN TINGKAT INOVASI PERUSAHAAN - Bayu Sindhu Raharja; Nur Laila Yuliani (Derivatif : Jurnal Manajemen, 2019)
This study examines the relationship between corporate governance in explaining the level of innovation of the company. The sample in this study uses companies that have a high level of liquidity in stock trading after the authoritarian era of the "New Order". This study uses a regression analysis tool to test the relationship between the two variables. As a result, this study found that corporate governance is an important factor that influences corporate innovation. The measuring instrument used to measure corporate governance in this study is the total number of commissioners in the company. The results of this study state that the total number of commissioners or corporate governance has a positive effect on the level of innovation of the company. This finding is very important for practitioners, especially for company managers who want to develop their company's innovations. While in the theoretical aspects, these findings strengthen the theory relating to corporate governance. Keywords: Keganenan theory, Principal-Agent Theory, Commissioner, Investment